Bryophytes Floristic Patterns in the Sicilian Aquatic and Humid Habitats—Important Refuges for Biodiversity Safeguarding in the Mediterranean Islands - Patrizia Campisi; Mattia Letizia Marino (Plants)
In this study, a focus on the populations of bryophytes living in aquatic and humid habitats of Sicily is presented. This investigation aims to evaluate the consistency and diversity of this group of taxa. The complete list of taxa known to date in these habitats is provided, with reference to hornworts, liverworts, and mosses, and the patterns related to the biological, ecological, and chorological features of this bryophyte flora are also illustrated. Since climate change is currently the major threat of extinction for many of these species growing in aquatic and humid environments, these taxa constitute a component of the flora worthy of particular interest in studies on the quantification of the impact of global warming on biodiversity. Overall, the analysis found that, with a total of 224 taxa, this group constitutes 36% of the Sicilian bryophyte flora; it is quite diversified from a taxonomic point of view, being represented by 55 families and 106 genera. Related to ecological features and reproductive biology, some aspects of possible vulnerability are highlighted, as well as others of resilience. Moreover, the importance of future monitoring of these taxa is underlined, also in consideration of the fact that some of them, such as Sciuro-hypnum ornellanum, are species of conservation interest in Italy and in Europe, and that four other taxa are threatened in Italy.